Finansowe determinanty niedoskonałości rynku nieruchomości - Półtorak, Bogusław (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
In this paper, the author discussed the development of real estate market in Poland and its finance institutions, the economic, legal, and financial solutions. On this market are present above all: people, developers, housing co-operatives, and local self-government entities. There have been more and more tight relations between financial system and residential market, especially between interest rates and residential demand. The development of real estate sector is one of the most important parts of the economic development. The aim of this paper is identification and description of financial determinants of the real estate market. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (16); 2008; nr 1193, s. 289-299